Prison-based education and re-entry into the mainstream labor market - John H. Tyler; Jeffrey R. Kling (Brown University, Department of Economics, 2004)
We estimate the post-release economic effects of participation in prison-based General Educational Development (GED) programs using a panel of earnings records and a rich set of individual information from administrative data in the state of Florida. Fixed effects estimates of the impact of participating in the GED education program show post-release quarterly earnings gains of about 15 percent for program participants relative to observationally similar nonparticipants. We also show, however, that these earnings gains accrue only to racial/ethnic minority offenders and any GED-related earnings gains for this group seem to fade in the third year after release from prison. Estimates comparing offenders who obtained a GED to those who participated in GED-related prison education programs but left prison without a GED show no systematic evidence of an independent impact of the credential itself on post-release quarterly earnings. – Incarceration ; GED ; Earnings
Keywords: J31; J38; 330; Straffälligenhilfe; Bildung; USA; Berufliche Integration